Supporting group collaboration in an annotation system. (August 2017) - Avola, Danilo; Bottoni, Paolo; Hawash, Amjad
Highlights: Group-based services supporting cooperation introduced to a Web annotation tool. Formal model of groups, of operations on them and of security mechanisms. Details on the overall architecture and core implementation mechanisms. Presentation of Technology-Enhanced Learning applicative scenarios and experimental tests. Abstract: Annotation has become a common practice when interacting with digital documents, allowing the addition of information to existing data without corrupting them. Restricting visibility of annotations to groups of users, as usually enforced in enterprise collaboration systems, turns annotations into a tool for focused collaboration among users with common interests. However, providing different levels of visibility in an open Web-based environment is challenging, due to conflicting needs: to keep the annotation process simple, to ensure adequate levels of privacy and confidence to users, and to allow users to filter out irrelevant information. We describe a suite of services for group formation and management, integrated into the existing MADCOW annotation system. We also propose a formal characterisation of groups, introducing atomic operations on which complex functionalities are based. The paper discusses different scenarios and applications and argues for the usability of the proposed integration by presenting the results of experimental tests.